INVESTIGATING THE EFFICACY OF DIAGNOSTIC ULTRASOUND IN DETECTING OCCULT INGUINAL HERNIA AMONG INGUINAL PAIN PATIENTS: A SINGLE-CENTRE INCIDENCE EVALUATION STUDY - Dr Kailash Kumar Daseja; Dr. Mohsin Hussain; Dr Din Muhammad Sohu; Dr. Nadia Bhatti; Dr Altaf-U-Rehman Sodhar; Dr Anzar Farooq Shaikh (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: To determine the frequency of occult inguinal hernia identified through ultrasound among individuals presenting with inguinal pain.Materials and Methods: This descriptive observational study assessed the presence of occult inguinal hernias in 90 male patients with chronic recurrent inguinal pain at Department of Radiology, Chandka Medical College Hospital, Shaheed Muhtarma Benazeer Bhutto Medical University, Larkana, Pakistan in the duration from March,2023 to February, 2024. Total Patients aged 18 to 80 years were included, excluding those with visible hernias. Written consent was obtained, and the study was approved by the institutional ethical committee. Patients underwent physical examinations and ultrasonographic evaluations using a 5-10 MHz linear probe. Diagnostic criteria for groin hernias on ultrasound included visualization of a hernia sac containing bowel or omentum and a positive cough/Valsalva impulse.Results: In a study involving 90 consecutive male patients with groin pain, the mean age was 53.1±15.7 years. Of these patients, 22.22% experienced bilateral groin pain, 36.67% had left-sided pain, and 41.11% reported right-sided pain. Further assessment identified occult inguinal hernias in 32.2% of the patients, with bilateral involvement in 10.34%, left-sided hernias in 24.14%, and right-sided hernias in 65.52%. Analysis of hernia defect sizes revealed a mean size of 3.25 mm on the right side and 4.89 mm on the left side among patients with occult hernias.Conclusion: It is evident that ultrasound emerges as a cornerstone in the diagnosis of occult inguinal hernias, offering clinicians a reliable means to identify and manage these conditions effectively. By leveraging ultrasound alongside thorough clinical examination, healthcare providers can ensure accurate diagnosis and tailored treatment plans for patients presenting with groin pain.